Kontribusi Ajaran Islam Terhadap Penguatan Ketahanan Keluarga Muslim Di Masa Modern - Ramadhan, Rahmad (YPI Ulul Albab, 2025)
This study aims to analyze family resilience from an Islamic perspective and to examine how Islamic values contribute to strengthening the foundations of the family amid rapid modernization. Employing a descriptive qualitative method based on a comprehensive literature review of national regulations, classical and contemporary tafsir, and scholarly opinions, the research explores key components of family resilience across structural, spiritual, moral, and social dimensions. The findings reveal that the concept of family resilience in Islam aligns with national legal frameworks that view the family as a dynamic institution responsible for maintaining harmony and well-being. Islamic principles such as spirituality, ethical conduct, balanced role distribution, and effective communication play a significant role in fostering a sakinah family capable of adapting to social and technological changes. Furthermore, the study highlights that the practical application of religious values including character building, communication enhancement, role optimization, and spiritual internalization directly contributes to the development of resilient Muslim families that can face contemporary challenges with greater strength, adaptability, and constructive capacity.